Arrival of steamboat SEATTLE NO. 1 at Dawson, Yukon Territory, 1898 - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Photographed at midnight, arrival of Seattle No. 1 at Dawson City, N.W.T. copyright 1898" Original photograph by Eric A. Hegg 701; copied by Larss and Duclos. Klondike Gold Rush.